Cultural Kasi’preneurs of Daveyton: cultural entrepreneurs and their processes of creating cultural value in the township - Motholo, Dimakatso (My University, 2020)
The cultural and creative industries in the townships are marginalized and often seen only as entertainment or hobbies, as a result, the key drivers of the cultural and creative industries, the cultural entrepreneur within the township economy is overlooked. Cultural entrepreneurs are thinking imaginatively about how they can add value to their townships. The Cultural entrepreneur is concerned with enhancing the livelihood and creating cultural value for both producers and consumers of their cultural products and services (Aageson, 2008). This research report focuses on identifying cultural entrepreneurs in the township of Daveyton, their businesses, and processes of creating cultural value. It places emphasis on the role and importance of networks in the process of value creation, how cultural entrepreneurs establish and develop these networks. The methods used to conduct the research were semi-structured interviews with eleven participants that are founders or co-founders of the business, as well as participant observation whereby participants were observed during their line of work. This research report also redefines the cultural entrepreneur in the township as a cultural kasi’preneur. The cultural kasi’preneur is finding alternative forms of existing, creating meaning, seeing, surviving, acquiring knowledge and skills
Submitted to the Faculty of Humanities, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Arts by Coursework and Research Report in the field of Cultural Policy and Management, 2020